sandy wrote:
\(a1, a2, a3 ................ an\)
In the sequence above, each term after the first term is equal to the preceding term plus the constant c. If \(a1+a3+a5=27\), what is the value of \(a2+a4\) ?
\(a2+a4=\)
By definition:
a1 = a1
a2 = a1 + c
a3 = a1 + c + c = a1 + 2c
a4 = a1 + c + c + c = a1 + 3c
a5 = a1 + c + c + c + c = a1 + 4c
GIVEN: a1+a3+a5=27We can write: a1 + (a1 + 2c) + (a1 + 4c) = 27
Simplify: 3a1 + 6c = 27
Divide both sides by 3 to get:
a1 + 2c = 9What is the value of \(a2+a4\) a2 + a4 = (a1 + c) + (a1 + 3c)
= 2a1 + 4c
= 2(
a1 + 2c)
= 2(
9)
= 18
Answer: 18
Cheers,
Brent